Dependency of B-1 Cells in the Maintenance of Splenic Interleukin-10 Producing Cells and Impairment of Macrophage Resistance in Visceral Leishmaniasis - Arcanjo, Angélica Fernandes; Nico, Dirlei; de Castro, Gabriellen Menezes Migliani; da Silva Fontes, Yasmin; Saltarelli, Paula; Decote-Ricardo, Debora; Nunes, Marise P.; Ferreira-Pereira, Antônio; Palatnik-de-Sousa, Clarisa B.; Freire-de-Lima, Célio G.; Morrot, Alexandre (Frontiers in Microbiology, 2017)
Visceral leishmaniasis (VL) is a neglected disease caused by Leishmania protozoa parasites transmitted by infected sand fly vectors. This disease represents the second in mortality among tropical infections and is associated to a profound immunossupression state of the host. The hallmark of this infection-induced host immunodeviation is the characteristic high levels of the regulatory IL-10 cytokine. In the present study, we investigated the role of B-1 cells in the maintenance of splenic IL-10 levels that could interfere with resistance to parasite infection. Using an experimental murine infection model with Leishmania (L.) infantum chagasi we demonstrated an improved resistance of B-1 deficient BALB/XID mice to infection. BALB/XID mice developed a reduced splenomegaly with diminished splenic parasite burden and lower levels of IL-10 secretion of purified splenocytes at 30 days post-infection, as compared to BALB/c wild-type control mice. Interestingly, we found that resident peritoneal macrophages isolated from BALB/XID mice were more effective to control the parasite load in comparison to cells isolated from BALB/c wild-type mice. Our findings point to a role of B-1 cells in the host susceptibility to visceral leishmaniasis.